Adoption of Virtual Reality Technology as a Strategy to Increase Purchase Intention - Salsabila Surya Motik; Weni Novandari (LP3M Universitas Putra Bangsa, 2025)
This study aims to examine the effect of Augmented Reality (AR) technology on users' purchase intention, with brand engagement as a mediating variable, among users of the IKEA Place application in Java Island. Employing a quantitative approach and a cross-sectional survey method, data were collected from 140 respondents who had used the AR feature in IKEA Place. The analysis was conducted using SEM-PLS. The results indicate that AR has a significant effect on both purchase intention and brand engagement. Furthermore, brand engagement is proven to significantly mediate the effect of AR on purchase intention. These findings affirm that the success of AR technology in enhancing purchase intention depends not only on its technological features, but also on the emotional engagement fostered by the brand.